A função do narrador como agenciador narrativo em ambientes tridimensionais imersivos em games de RPG - Silva, Alexandre Vieira da (2014)
The research aims to discuss the possibility of reducing the conflict between the drama of classic interactive media and freedom of digital media through the development of an electronic game focused on the narrator and the act of narration , introducing the concept of narrative management, contextualizing it within digital games and discussing the relevance of the presence of a narrator in real time intervening in the discourse . The discussion starts from the premise inserting a interactor , endowed with the functions of narrating and acting within the game , which has the task of managing immersive three-dimensional environments and conducting an interactive narrative experience with greater breadth and dramatic . Through participation in the narrative of human intelligence driving within the interactive medium , it seeks to reduce the verbal limitations of the media and create a favorable condition for the application of classical narrative structures in the digital environment . The research relies methodologically on two core elements: narrative structures applied to the digital medium , aligning the narrative and drama to new concepts such as procedural narrative classic elements and features of the digital narrative , and investigates the possibilities of introducing the figure of interactor / narrator in a new digital narrative structure , in which it is possible and in this game, player to reach a wider range of possibilities of meaning and narrative